2004
DOI: 10.1002/jmv.20248
|View full text |Cite
|
Sign up to set email alerts
|

Measles virus genotype circulation in Spain after implementation of the national measles elimination plan 2001–2003

Abstract: Molecular characterization of measles virus is important for disease surveillance and for monitoring elimination of the virus throughout the world. Furthermore, knowledge of genotype distribution in as many countries as possible, is useful for tracing the origin of a strain, especially in countries without endemic measles disease, where most cases are imported. Data on genotypes circulating in Spain from 1970 to 1997 showed the prevalence of genotypes C1, C2, and D6, with subsequent replacement of each other. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 22 publications
0
26
0
2
Order By: Relevance
“…Measles genotypes are not geographically confined; however, there are predominant circulating clades in certain areas. For example, in Italy and France the main reported genotype is D7 [Zandotti et al, 2004;Ciofi Degli Atti et al, 2006], whereas, other countries in Europe, such as in Germany and Spain, have reported the presence of a broad diversity of circulating strains genotypes B3, C2, D4, D5, D6, D7, G2, and H1 [Tischer et al, 2004;Mosquera et al, 2005] More recently during 2005 and 2006, in the World Health Organisation (Kremer et al, 2008) European Region major epidemics were associated with genotypes D4, D6, and B3, although other genotypes were found after importation from other continents (B2, D5, D8, D9, G2, and H1) [Kremer et al, 2008].…”
Section: Measles Virus (Mev) Is the Sole Member Of The Genusmentioning
confidence: 99%
“…Measles genotypes are not geographically confined; however, there are predominant circulating clades in certain areas. For example, in Italy and France the main reported genotype is D7 [Zandotti et al, 2004;Ciofi Degli Atti et al, 2006], whereas, other countries in Europe, such as in Germany and Spain, have reported the presence of a broad diversity of circulating strains genotypes B3, C2, D4, D5, D6, D7, G2, and H1 [Tischer et al, 2004;Mosquera et al, 2005] More recently during 2005 and 2006, in the World Health Organisation (Kremer et al, 2008) European Region major epidemics were associated with genotypes D4, D6, and B3, although other genotypes were found after importation from other continents (B2, D5, D8, D9, G2, and H1) [Kremer et al, 2008].…”
Section: Measles Virus (Mev) Is the Sole Member Of The Genusmentioning
confidence: 99%
“…D4 viruses are still endemic on the Indian subcontinent as well as in East and South Africa (5,27). Although some outbreaks and sporadic cases associated with genotype D4 had been reported from Europe, the corresponding viruses were mostly imported from other continents and differed considerably from the more recent strains (6,11,30). In 2005-2006, genotype D4 was found in 16 of the 27 countries in which MV has been genotyped; most of the corresponding viruses were related to the outbreak in Romania.…”
Section: Discussionmentioning
confidence: 96%
“…The low genetic diversity of D6 strains suggests that enhanced vaccination has largely reduced the cocirculation of highly diverse D6 variants in Europe. Moreover, genotypes C2 and D7, which were frequently identifi ed in Europe until 2004 (4)(5)(6)(7)(8)(10)(11)(12), were no longer found during the past 2 years, despite greatly improved virologic surveillance. Genotype C2 had been continuously identifi ed in the European Region since the early 1970s, and genotype D7 had partially replaced genotypes C2 and D6 in Germany during 2000-2004 (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these sequences, 24 genotypes have been identified [6,7]. Since 1998, the standard genotyping RT-PCR assay from the CDC recommended a primer pair designated MV60/MV63.3 [8] though other primers were also used throughout LabNet [9][10][11][12][13][14]. Several new MeV genotypes have been described since the introduction of the standard genotyping method [15][16][17]; however, only limited sequence data were available for the primer binding sites of the more recent strains and the analytic sensitivity of the primers had not been evaluated.…”
Section: Introductionmentioning
confidence: 99%